1993
DOI: 10.1083/jcb.120.5.1123
|View full text |Cite
|
Sign up to set email alerts
|

Localization of TGN38 to the trans-Golgi network: involvement of a cytoplasmic tyrosine-containing sequence.

Abstract: Abstract. Protein localization to the TGN was investigated by examining the subcellular distribution of chimeric proteins in which the cytoplasmic and/or transmembrane domains of the TGN protein, TGN38, were substituted for the analogous domains of the plasma membrane protein, Tac. Using immunofluorescence and immunoelectron microscopy, the COOHterminal cytoplasmic domain of TGN38 was found to be sufficient for localization of the chimeric proteins to the TGN. Deletion analysis identified an l 1-amino acid seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
237
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(270 citation statements)
references
References 78 publications
32
237
0
1
Order By: Relevance
“…Signals such as the C-terminal tetrapeptide KDEL (Munro & Pelham, 1987) retrieve soluble proteins from the Golgi complex back to the ER lumen. Also the tetrapeptide YQRL is sufficient for trans-Golgi localization of proteins (Humphrey et al, 1993). Testing the levansucrase sequence for the presence of known retention signals did not reveal the presence of known ER or Golgi retention signals.…”
Section: Discussionmentioning
confidence: 97%
“…Signals such as the C-terminal tetrapeptide KDEL (Munro & Pelham, 1987) retrieve soluble proteins from the Golgi complex back to the ER lumen. Also the tetrapeptide YQRL is sufficient for trans-Golgi localization of proteins (Humphrey et al, 1993). Testing the levansucrase sequence for the presence of known retention signals did not reveal the presence of known ER or Golgi retention signals.…”
Section: Discussionmentioning
confidence: 97%
“…The YMPL motif resembles other Tyr-based motifs implicated in targeting to endosomes or the TGN and interaction with the clathrin-associated adaptor proteins (Bos et al, 1993;Humphrey et al, 1993;Wong and Hong, 1993;Ohno et al, 1995). Both of the Tyr-containing regions are conserved between AtELP and the maize EST clone.…”
Section: Dlscusslonmentioning
confidence: 99%
“…As an additional assay to better determine whether TOCA/CDC-42/PAR/WAVE proteins are required for transport of cargo from recycling endosomes to the TGN, we focused a set of experiments on TGN-38, the C. elegans homolog of mammalian TGN38/TGN46 (40)(41)(42). We focused on TGN-38 because previous work in mammalian cells showed that when its recycling is blocked, TGN38 accumulates in the compartment from which its budding is impaired, and because TGN38 is transported from the plasma membrane to the TGN via recycling endosomes (endocytic recycling compartment) in the well-studied CHO cell model (20, 22-24, 43, 44).…”
Section: Loss Ofmentioning
confidence: 99%